Optimal Routing Protocol in Multimedia Wireless Sensor Networks - Al-Zurba, Hiba (2011)
A Master of Science Thesis in Computer Engineering Submitted by Hiba Al-Zurba entitled, "Optimal Routing Protocol in Multimedia Wireless Sensor Networks," January 2011. Available are both soft and hard copies of the thesis.